1998
DOI: 10.1086/311755
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Double Magnetic Cycle of the Sun

Abstract: It has been argued that the solar magnetic cycle consists of two main periodic components: a low-frequency component (Hale's 22-year cycle) and a high-frequency component (quasi-biennial cycle). The existence of the double magnetic cycle on the Sun is confirmed using Stanford, Mount Wilson and Kitt Peak magnetograph data from 1976 to 1996 (solar cycles 21 and 22). In the frame of the Parker's dynamo theory a model of the double magnetic cycle is presented. This model is based on the idea of two dynamo sources … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
16

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 14 publications
3
64
0
16
Order By: Relevance
“…The different behaviors of ∂Ω/∂r at high and low latitudes suggests the presence of two activity belts in which magnetic tracers migrate along in opposite directions. Such an approach agrees with the observations of latitude migration of several indicators of solar activity during the Schwabe cycle (Benevolenskaya 1998). In fact, sunspots and faculae, observed in the activity belts, migrate toward the equator while polar prominences (e.g., Benevolenskaya et al 2001) and coronal emissions (see Rusin et al 1998) migrate poleward, likely within a 2-3 yr time period.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The different behaviors of ∂Ω/∂r at high and low latitudes suggests the presence of two activity belts in which magnetic tracers migrate along in opposite directions. Such an approach agrees with the observations of latitude migration of several indicators of solar activity during the Schwabe cycle (Benevolenskaya 1998). In fact, sunspots and faculae, observed in the activity belts, migrate toward the equator while polar prominences (e.g., Benevolenskaya et al 2001) and coronal emissions (see Rusin et al 1998) migrate poleward, likely within a 2-3 yr time period.…”
Section: Introductionsupporting
confidence: 86%
“…This component of the cycle, although weaker than the main component, has been identified in many activity indices (Rao 1973;Valdés-Galicia et al 1996;Bazilevskaya et al 2000;Kudela et al 2002;Bai 2003;Knaack & Stenflo 2005;Vecchio & Carbone 2008, 2009). The QBO origin is still unknown even if it could be related to the dynamo action in the inner solar layers (Benevolenskaya 1998), being also detected in phenomena directly connected with the solar interior. In fact, the equatorial rotation rate close to the tachocline varies with a 1.3 yr period (Howe et al 2000), as detected from GONG and MDI observations (although it is not confirmed after 2001; Howe 2009) as well as the solar angular momentum (Komm et al 2003); the solar neutrino flux shows a significant modulation at the QBO rate (Vecchio et al 2010); a ∼2 yr signal has been detected for the natural p-mode frequencies of the Sun (Fletcher et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this periodicity represents the highest amplitude mode (j = 8, τ 8 = 21 ± 7 yr) in the HMF magnitude. The CLI mode j = 7 (τ 7 = 6.5 ± 0.5 yr) is found to be the third most prominent mode, while IMFs with τ j at the typical QBOs timescales (Benevolenskaya 1998;Bazilevskaya et al 2000Bazilevskaya et al , 2006 have lower amplitudes (j = 4, j = 5, and j = 6 with periods τ 4 = 1.31±0.04 yr, τ 5 = 2.19 ± 0.09 yr, and τ 6 = 3.5 ± 0.3, respectively). Mode j = 10, with τ 10 ∼ 40 yr, shows only one oscillation, whose τ j cannot be considered as reliable, given the limited time extent of the data set.…”
Section: Data Used and Methods Of Investigationmentioning
confidence: 89%
“…The literature contains examples of the quasibiennial variations, better known as quasi-biennial oscillations (QBOs, see e.g. Gnevyshev 1977;Benevolenskaya 1998;Kane 2005). Similar variations within the same time interval are found in many geophysical processes (see e.g.…”
Section: Introductionmentioning
confidence: 96%